The structured ambulatory post-stroke care program for outpatient aftercare in patients with ischaemic stroke in Germany (SANO): an open-label, cluster-randomised controlled trial. - Schwarzbach, Christopher J.; Eichner, Felizitas Anna; Rücker, Viktoria; Hofmann, Anna Lena; Keller, Moritz; Audebert, Heinrich J.; von Bandemer, Stephan; Engelter, Stefan T.; Geis, Dieter; Gröschel, Klaus; Haeusler, Karl Georg; Hamann, Gerhard F.; et al. (Lancet Neurology, 2023)
BACKGROUND: Patients with ischaemic stroke are at risk of recurrent stroke. In this study, we aimed to compare the effect of a structured ambulatory post-stroke care programme versus usual care on recurrent vascular events and death and control of cardiovascular risk factors. METHODS: We did a prospective, open-label, cluster-randomised controlled trial (SANO) at stroke centres in regions of Germany. A cluster was defined as a region in which acute stroke care is provided by a participating stroke centre. Patients were eligible for participation if they were aged 18 years or older, had no severe disabilities before the index stroke (modified Rankin scale 0-1), had at least one modifiable cardiovascular risk factor, and presented within 14 days of symptom onset of their first ischaemic stroke. The participating regions were randomly assigned (1:1) to the intervention and control group (usual care) by the statistician using block randomisation (block sizes of six), stratified by rural and urban regions. In intervention regions, a cross-sectoral multidisciplinary network was established to provide a 1-year organisational and patient-centred intervention. Due to the type of intervention, masking of participants and study physicians was not possible. Endpoint adjudication was performed by an independent endpoint adjudication committee who were masked to cluster allocation. The primary endpoint was a composite of recurrent stroke, myocardial infarction, and all-cause death within 12 months after baseline assessment, assessed in the modified intention-to-treat (mITT) population, which included all patients who did not withdraw consent and completed the primary endpoint assessment at 12 months. This study was registered with the German Clinical Trials Register, DRKS00015322. FINDINGS: Between Jan 1, 2019 and Dec 22, 2020, 36 clusters were assessed for eligibility, of which 30 were randomly assigned to the intervention group (n=15 clusters) or control group (n=15 clusters). No clusters dropped out of the study. 1203 (86%) of 1396 enrolled patients in the intervention group and 1283 (92%) of 1395 enrolled patients in the control group were included in the mITT population. The primary endpoint was confirmed in 64 (5·3%) of 1203 patients in the intervention group and 80 (6·2%) of 1283 patients in the control group (unadjusted odds ratio [OR] 0·80 [95% CI 0·49-1·30]; adjusted OR [aOR] 0·95 [95% CI 0·54-1·67]). All-cause deaths occurred in 31 (2·4%) of 1203 patients in the intervention group and 12 (1·0%) of 1283 patients in the control group. The incidence of serious adverse events was higher in the intervention group (266 [23·1%] of 1151) than the control group (106 [9·2%] of 1152). Falls (134 [11·4%] of 1203 patients in the intervention group; 39 [3·3%] of 1152 patients in the control group), hypertensive crisis (55 [4·7%]; 34 [2·8%]), and diagnosis of depression (51 [4·3%]; 13 [1·1%]) were the most frequent adverse events in both groups. No differences were identified in the rate of readmission to hospital between groups. INTERPRETATION: No differences were identified between patients with ischaemic stroke in the intervention group and control group with regard to the incidence of vascular events 1 year after baseline assessment, despite positive effects with regard to the control of some cardiovascular risk factors. Longer-term effects and other potentially favourable effects on stroke-related sequelae and quality of life require further evaluation. FUNDING: Innovation Fund of the Federal Joint Committee.
EVALuna2:546728